Overexpression of a novel heat-inducible ethylene-responsive factor gene LlERF110 from Lilium longiflorum decreases thermotolerance. (June 2022) - Li, Ting; Wu, Ze; Xiang, Jun; Zhang, Dehua; Teng, Nianjun
Abstract: AP2/ERF (APETALA2/ethylene-responsive factor) family transcription factors are involved in various plant-specific processes, especially in plant development and response to abiotic stress. However, their roles in thermotolerance are still largely unknown. In the current study, we identified a heat-inducible ERF member LlERF110 from Lilium longiflorum that was rapidly induced by high temperature. Its protein was localized in the nucleus, and transcriptional activation activity was observed in yeast and plant cells. In addition, LlERF110 was able to bind to GCC- and CGG-elements, but not to DRE-elements. Overexpression of LlERF110 conferred delayed bolting and bushy phenotype, with decreased thermotolerance accompanied by a disrupted ROS (reactive oxygen species) homeostasis in transgenic plants. The accumulation of LlERF110 may activate certain repressors related to heat stress response (HSR) and indirectly damage the normal expression of heat stress (HS)-protective genes such as AtHSFA2, which consequently leads to reduced thermotolerance. Our results implied that LlERF110 might function as a heat-inducible gene but may hinder the establishment of thermotolerance. Highlights: LlERF110 is an heat-inducible ERF transcription factor of the group X (B-4) subfamily. LlERF110 functions in the nucleus as a transcriptional activator. LlERF110 binds to GCC-box and CGG-box elements. Overexpression of LlERF110 causes delayed bolting and bushy phenotype. Overexpression of LlERF110 damages thermotolerance accompanied by a disrupted ROS homeostasis.